A Non-equilibrium Approach to Model Flash Dynamics with Interface Transport. Issue 18 (2018) - Romo-Hernandez, Aarón; Dochain, Denis; Ydstie, B. Erik; Hudon, Nicolas
Abstract: This paper presents a modeling approach for a class of multiphase chemical systems, based on non-equilibrium thermodynamics, specialized to an open flash-drum system. A compartmental model is considered to establish the dynamics of the gas and liquid phases, while a model of interface transport yields to constraints in the model. The overall system is thus written as a Differential-Algebraic system of Equations (DAE). The derived model is shown to be of index one, for which a stability analysis, based on Lyapunov first method, is briefly developed. An example is presented to illustrate the proposed modeling and stability analysis approach, together with numerical simulations.